Project management workbook and PMP/CAPM exam study guide - Kerzner, Harold (John Wiley & Sons, Inc., 2013)
This is the Eleventh Edition of the student workbook that accompanies the best selling ""bible"" of project management. The workbook contains additional problems and exercises to reinforce the concepts presented in the main text. It also serves as a self-study guide for the Project Management Professional (PMP) certification exam to be based on PMI's PMBOK Guide, 5E. Both as accompanying supplement to Kerzner's text and as standalone self-study guide, this workbook gives students key insights from the acknowledged world leader in project management.